On Interval-Valued Intuitionistic Fuzzy Hyper BCK-Ideals of Hyper BCK Algebras - Satyanarayana, B.; Krishna, L.; Prasad, R. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we apply the concept of an interval-valued intuitionistic fuzzy set to hyper BCK-ideals in hyper BCK-algebras. The notion of an interval-valued intuitionistic fuzzification of (strong, weak, s-weak) hyper BCK-ideals is introduced, and related properties are investigated. Characterizations of an interval-valued intuitionistic fuzzification of hyper BCK-ideals are established.